News framing in the promotion of fear: Media coverage of the terrorist attacks of November 13, 2015, in Paris and November 22, 2016, in Brussels - Estêvão, T.; Espanha, R. (Observatorio (OBS*), 2025)
The framing of the news associated with terrorism has been investigated as an academic subject in different areas of the social sciences. By applying interpretative schemes, the media classify and interpret the information that reaches us on a daily basis. They influence audience perceptions of terrorism by highlighting, devaluing or omitting certain issues and subjects. This article focuses on the issue news framing associated with terrorism, first identifying the prevalent frames evidenced in news coverage in Portugal of terrorist attacks in Europe. Secondly, the article discusses how the prevalent frames adopted, identified in the research, enable the feeling of fear of terrorist attacks.